Pengembangan Assistive Electric Vehicles untuk Penyandang Disabilitas Fisik - Mais, Asrorul; Yaum, Lailil Aflahkul; Adi, Partiwi Ngayuningtyas; Ariyanto, Dedy (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine the technical specifications of electric motorbikes needed by people with physical disabilities and realize this by developing assistive devices in the form of Assistive Electric Vehicles. The Assistive Electric Vehicle development method for physical disabilities is carried out using the ADDIE (Analysis-Design-Develop-Implement-Evaluate) design and development model which is integrated according to the research and development steps recommended by Borg and Gall on the basis of consideration that this model is suitable for developing a product or a valid, effective, and efficient model. Research results obtained that. Based on the results of trial 1, it obtained a percentage of 80.71% and the results of trial II obtained an average percentage of 88.57%. Based on the results of the validation team and the results of the trials, the conclusions obtained from the results of the successful development of this product are categorized as very feasible and can be used easily and comfortably by persons with disabilities. Keywords: Assistive, Electric Vehicle and Physical Disabilities